HISTOLOGICAL STRUCTURE AND HISTOMORPHOMETRY OF THE BALI DUCK OESOPHAGUS IN STARTER PHASE - Hutapea, Eunike Beallara; Setiasih, Ni Luh Eka; Laksmi, Desak Nyoman Dewi Indira; Heryani, Luh Gde Sri Surya; Susari, Ni Nyoman Werdi; Widyastuti, Sri Kayati (Buletin Veteriner Udayana, 2025)
Bali duck (Anas sp.) is a native Indonesian duck breed developed in the Bali and Lombok regions. Bali duck have significant potential as producers of eggs and meat, contributing to the fulfilment of animal protein needs of the Indonesian population. This study was conducted to determine the histological structure and histomorphometry of the oesophagus of bali duck during the starter phase. Samples were taken from ducks aged 1 day, 14 days, 28 days, 42 days, and 56 days. Histological sample observations focused on the layers composing the oesophagus. Parameters used for histomorphometry measurements were the thickness of the oesophageal tunica layers and he results of the research on histological structure are presented in a descriptive qualitative form. The results of the research on histomorphometry are presented in a descriptive quantitative form, analysed using Analysis of Variance (ANOVA) and if the results showed a significant difference, were followed by Duncan’s post-hoc test. The study results indicated that histologically, the bali duck oesophagus consists of the tunica mucosa, tunica submucosa, tunica muscularis, and tunica adventitia. Histomorphometry results showed an increase in the thickness of each layer with increasing age, from 1 day, 14 days, 28 days, 42 days, to 56 days. Further studies in different phase employing special staining techniques are required to allow for more detailed identification.